2018
DOI: 10.3390/cells7110192
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Activity and Molecular Docking of Novel Double-Modified Colchicine Derivatives

Abstract: Microtubules are tubulin polymer structures, which are indispensable for cell growth and division. Its constituent protein β-tubulin has been a common drug target for various diseases including cancer. Colchicine has been used to treat gout, but it has also been an investigational anticancer agent with a known antimitotic effect on cells. However, the use of colchicine as well as many of its derivatives in long-term treatment is hampered by their high toxicity. To create more potent anticancer agents, three no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…However, the use of colchicine as well as many of its derivatives in long-term treatment is hampered by their dose-limiting high toxicity. To create more potent anticancer agents, three novel double-modified colchicine derivatives have been synthesized by structural modifications, as discussed by Majcher et al in one of the papers in this Special Issue [5]. The binding affinities of these derivatives of colchicine with respect to eight different isotypes of human β-tubulin have been calculated using homology models of these tubulin isotypes combined with docking methods for the interactions with the ligands.…”
Section: Novel Tubulin-targeting Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of colchicine as well as many of its derivatives in long-term treatment is hampered by their dose-limiting high toxicity. To create more potent anticancer agents, three novel double-modified colchicine derivatives have been synthesized by structural modifications, as discussed by Majcher et al in one of the papers in this Special Issue [5]. The binding affinities of these derivatives of colchicine with respect to eight different isotypes of human β-tubulin have been calculated using homology models of these tubulin isotypes combined with docking methods for the interactions with the ligands.…”
Section: Novel Tubulin-targeting Drugsmentioning
confidence: 99%
“…The inhibition of proteins with an anti-apoptotic function, which is often overproduced in tumors, may therefore improve the effect of anti-microtubular drugs. The development of new drugs could involve the generation of derivatives of existing compounds which could endow them with a higher anticancer potential using state-of-the-art approaches based on a knowledge of molecular biology of tubulin structures in combination with computer-aided drug design, which has been demonstrated in one of the papers in this issue [5].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, semisynthetic derivatives that present lower toxicity have been developed and successfully applied on in vitro studies. Colchicinamide, deacetylcolchicine or valyl colchicine and other synthetic derivatives have been tested in different in vitro human cancer cell lines such as colorectal, chronic granulocytic leukemia, melanoma, central nervous system and breast cancers [ 36 , 91 , 92 , 93 ]. It seems that deacetylcolchicine has been employed in clinical trials, due to its effectiveness against melanoma, Hodgkin’s lymphoma, and chronic granulocytic leukemia [ 94 ], but, to our knowledge, no other clinical trials with colchicine derivatives have been reported.…”
Section: Compounds In Pre-clinical and Clinical Stagesmentioning
confidence: 99%
“…AutoDock V4.2 uses a computationally inexpensive "hybrid" force field that covers terms based on molecular procedure as well as experiential terms [21]. The calculation of absolute binding energies may be less precise compared to more computationally expensive, purely force field-based approaches, but this semi-empirical approach is measured as well-suited for the relative rankings as shown in Table 3.…”
Section: Molecular Dockingmentioning
confidence: 99%